Estudio de la optimización de la calidad del abono bocashi mediante la adición de potenciales microorganismos eficaces - Rueda Moreno, Richard Javier (2017)
The research was carried at the Treatment and Disposal Center of solid waste “Romerillos” of the Municipal GAD of Mejia Canton, place where it is elaborated organic fertilizer Bocashi based on plants material which is recovered in the filling, the purpose of the project was to optimize the quality of the fertilizer using Effective Microorganisms of natural origin presenting on natural ecosystems, Facilitating the decomposition of organic waste. For obtaining the microorganisms were placed traps in the natural forest “Rumiñahui” for a period of 15 days and a portion of soil was collected with organic matter for the multiplication of autochthonous microorganisms, then the traps were moved to a suitable place for reproduction observing that the species collected were the genres Trichoderma spp. of dark green color and Bacillus spp. whitish color. The reproduction of these species was carried out in containers mixing water with molasses and autochthonous microorganisms were proliferated submerging a sock nylon with soil and organic matter in the mixture of milk, molasses and yeast during 15 days obtaining a solution, because the molasses provides energy to the microorganisms. The solution was added on the organic matter during the first two weeks in all three treatments starting the process of producing the fertilizer controlling the temperature to approximately 60oC doing three turns per week and ending with the process at 42 days. Through the report results it was determined that the microorganism that helped mainly in the optimization of the fertilizer was the genus Bacillus spp. obtaining a total of 400 million cfu/gr, increasing its nutritional quality by 27%, because the bacteria have the ability to multiply rapidly by colonizing the substrate and maintained until the end the production process of the Bocashi fertilizer. With the use of these microorganisms the structure and quality of the soil can be improved reducing costs, time and chemicals products.